THE EFFECTS OF PROBENECID ON THE EXCRETION KINETICS OF STANOZOLOL, AN ANABOLIC-STEROID, IN RATS - RYU, JC; KWON, OS; SONG, YS; YANG, JS; PARK, JS (JOHN WILEY & SONS LTD, 1992)
The pharmacokinetic behaviour and the mechanism of renal excretion of stanozolol (STZ), as affected by co-treatment with probenecid, were studied in male Sprague-Dawley rats. Pharmacokinetic parameters following intravenous (i.v.) administration of STZ (20 mg kg-1 body wt.) were measured in both STZ-treated (control) and STZ plus probenecid-treated (treatment) groups. In order to assess the renal clearance of STZ, bolus doses of STZ and inulin (40 mg kg-1 body wt.) were injected i.v. either in the presence or absence of probenecid (40 mg kg-1 body wt.). The blood and urine concentrations of STZ were determined by capillary gas chromatography-mass spectrometry (GC-MS). In the probenecid treatment group, the area under the plasma disappearance and urinary excretion curves (AUC) of STZ were significantly decreased (P < 0.01) and the volume of distribution (V(d)) and total clearance (CL(t)) were significantly increased statistically (P < 0.05 and P < 0.01, respectively). No remarkable differences in the urine flow rate, urine pH values, glomerular filtration rate (GFR) or renal clearance were observed in the treatment group. However, the clearance ratio in the treatment group was significantly increased from 11.72 to 17.27. From these results, it is suggested that the significant decrease of AUC, i.e. increase of disappearance of STZ in plasma by co-administration with probenecid, is due to the increase of the clearance ratio.